A study on knowledge, attitude and practice about organ donation among college students in Telangana state - Kumar, Parepalli Vinay; Jothula, Kishore Y. (International Journal Of Community Medicine And Public Health, 2019)
Background: The change of disease pattern from communicable to non communicable or chronic diseases leading to end stage organ damage has led to the increase in the requirement of organ transplantation. Though the quality of organ transplantation has improved, the organ transplantation rate in India is 0.26 per million. Such a low rate is due to the lack of knowledge and misconception about organ donation. Methods: A pre-tested, semi-structured questionnaire was prepared, participants were chosen at random from the study population, they were interviewed with the questionnaire and their responses were computed and analysed. Results: In this study population, all of them knew about organ donation. The study shows that 62.7% of the students have adequate knowledge about organ donation. 67% of them would like to donate organs in future and 85% were willing to motivate their family to be an organ donor. Conclusions: The present rate of organ transplantation would be improved only when the society is educated with the knowledge, uncover the myths and misconceptions. It is also important that the organizations as to where and how to approach for the donation is known to all. Media being a powerful weapon of the generation can be a great tool to reach the society.